The Performance of City/Regency Councils in Achieving Good Governance in the Special Capital Region of Jakarta - Amatulloh, Putra Amin; Izzatusholekha, Izzatusholekha (Devotion : Journal of Research and Community Service, 2026)
This study aims to analyze the performance of City/Regency Councils in realizing Good Governance in the Special Region of Jakarta based on five indicators according to Dwiyanto (2008), namely, productivity, service quality, responsiveness, responsibility, and accountability. The main problems found are weak work standards, lack of transparency, and suboptimal coordination with local governments due to the absence of regulations governing the City Council secretariat. This study uses a descriptive method with qualitative data, data collection through in-depth interviews, field observations, and analysis of official documents. The results of the study show that the productivity of the City Council is still low because there are no clear Key Performance Indicators (KPIs). The quality of service varies due to the absence of standard operating procedures (SOPs). Responsiveness is quite good in following up on people's aspirations, but it has not been supported by a standard evaluation system. Responsibility is disrupted by weak coordination with local governments due to the absence of a Governor's Regulation (Pergub) that regulates the operations of the City Council. Accountability is also an obstacle because public access to performance reports is still limited. The conclusion of this study emphasizes that the performance of the City Council needs to be improved through service standardization, digitization of the public complaint system, and increased transparency through the publication of periodic reports. With these improvements, the City/Regency Council is expected to play a more effective role in supporting Good Governance in Jakarta